Familial aggregation of stillbirth: A pedigree analysis of a matched case–control study. (9th October 2022) - Workalemahu, Tsegaselassie; Page, Jessica M.; Meeks, Huong; Yu, Zhe; Guinto, Emily; Fraser, Alison; Varner, Michael W.; Theilen, Lauren H.; Quinlan, Aaron; Coon, Hilary; Enquobahrie, Daniel A.; Ananth, Cande V.; et al.
Abstract: Objective: To determine whether stillbirth aggregates in families and quantify its familial risk using extended pedigrees. Design: State‐wide matched case–control study. Setting: Utah, United States. Population: Stillbirth cases ( n  = 9404) and live birth controls (18 808) between 1978 and 2019. Methods: Using the Utah Population Database, a population‐based genealogical resource linked with state fetal death and birth records, we identified high‐risk pedigrees with excess familial aggregation of stillbirth using the Familial Standardised Incidence Ratio (FSIR). Stillbirth odds ratio (OR) for first‐degree relatives (FDR), second‐degree relatives (SDR) and third‐degree relatives (TDR) of parents with a stillbirth (affected) and live birth (unaffected) were estimated using logistic regression models. Main outcome measures: Familial aggregation estimated using FSIR, and stillbirth OR estimated for FDR, SDR and TDR of affected and unaffected parents using logistic regression models. Results: We identified 390 high‐risk pedigrees with evidence for excess familial aggregation (FSIR ≥2.00; P ‐value <0.05). FDRs, SDRs and TDRs of affected parents had 1.14‐fold (95% confidence interval [CI]: 1.04–1.26), 1.22‐fold (95% CI 1.11–1.33) and 1.15‐fold (95% CI 1.08–1.21) higher stillbirth odds compared with FDRs, SDRs and TDRs of unaffected parents, respectively. Parental sex‐specific analyses showed male FDRs, SDRs and TDRs of affected fathers had 1.22‐fold (95% CI 1.02–1.47), 1.38‐fold (95% CI 1.17–1.62) and 1.17‐fold (95% CI 1.05–1.30) higher stillbirth odds compared with those of unaffected fathers, respectively. FDRs, SDRs and TDRs of affected mothers had 1.12‐fold (95% CI 0.98–1.28), 1.09‐fold (95% CI 0.96–1.24) and 1.15‐fold (95% CI 1.06–1.24) higher stillbirth odds compared with those of unaffected mothers, respectively. Conclusions: We provide evidence for familial aggregation of stillbirth. Our findings warrant investigation into genes associated with stillbirth and underscore the need to design large‐scale studies to determine the genetic architecture of stillbirth. Abstract : Linked article :This article is commented on by Matthew A. Shear, pp. 463 in this issue. To view this mini commentary visit https://doi.org/10.1111/1471-0528.17365